Evaluation of the antidiabetic property of capparis ovata desf. Var. Palaestina zoh. Extracts using in vivo and in vitro approaches - Okur, Mehmet Evren; Çiçek Polat, Derya; Özbek, Hanefi; Yılmaz, Sezen; Yoltaş, Ayşegül; Arslan, Rana (Bentham Science Publ Ltd, 2018)
Background and Objective: This paper is focused on evaluating the various biological activities of C. ovata var. palaestina extracts which could beneficially influence diabetes and its complications. Methods: Alloxan-induced diabetic BALB-c mice were administered intraperitoneally with 100, 300, 500mg/kg doses of ethanol and aqueous extracts of buds and fruits. Furthermore, HPLC, phenolic and flavonoid compounds analysis, ABTS and DPPH free radical scavenging activity, anti-inflammatory activity, agar well diffusion and MIC tests were carried out. Results: Fruit-aqueous; 100mg/kg, 300mg/kg and bud-aqueous; 500mg/kg extracts showed significant hypoglycemic activity. All extracts indicated important antioxidant activity, however, bud-aqueous extract demonstrated the most potent activity. HPLC study exhibited that rutin is found in high amounts in bud-aqueous and bud-ethanol extracts. Furthermore, the bud-aqueous extract depicted stronger and broader antimicrobial activity than other extracts. Fruit-ethanol and bud-ethanol extracts denoted the most potent anti-inflammatory effect even though this effect was significantly shown by all extracts. Finally, high levels of phenolic and flavonoid content were involved in all extracts, but the highest levels were found in fruit-ethanol and bud-ethanol extracts. Conclusion: The results showed that extracts which indicated hypoglycemic, antioxidant, anti-inflammatory, antimicrobial activities may provide a valuable contribution to the management of diabetes and its complications.
WOS: 000445417300007
PubMed ID: 29595118
Keywords: Diabetes Mellitus; C. Ovata Var Palaestina; Hypoglycemic Effect; Antioxidant; Antimicrobial; Hyperglycemia